Vitamin D3 improves the effects of low dose Der p 2 allergoid treatment in Der p 2 sensitized BALB/c mice. Issue 1 (December 2016) - Petrarca, Claudia; Clemente, Emanuela; Amato, Valentina; Gatta, Alessia; Cortese, Sara; Lamolinara, Alessia; Rossi, Cosmo; Zanotta, Stefania; Mistrello, Gianni; Paganelli, Roberto; Gioacchino, Mario
Abstract Background Airborne allergens can induce an immunological chronic disease characterized by airway hyper responsiveness and inflammation, mediated by exaggerated Th2 immune response. Allergen-specific immunotherapy (AIT) is effective for treating this condition because it is able to modify its natural course by opposing the underlying pathogenic mechanisms and determining immune suppression, immune deviation and tolerance. The rational for the present study was to investigate the possibility of improving allergoid-based IT in terms of efficacy and safety. Recently, 1α, 25-dihydroxyvitamin D3 (VD3 ), the active metabolite of vitamin D3, was described to be a potent inducer of T regulatory cells and to be a good adjuvant in AIT settings. Methods We investigated whether the co-administration of VD3 could potentiate the effect of AIT even when added to a low dose of chemically-modified monomeric allergoid of Der p 2 (d2-OID), in a Derp p 2 (d2)-sensitized BALB/c mice model. Control groups where treated with sham, VD3 alone or d2-OID only. Results The d2-OID alone was not fully successful, as expected for a low dose. VD3 administration was associated with some valuable, although limited, changes in the immunological parameters in the lung. On the contrary, the VD3 adjuvated allergoid vaccine induced the most prominent reduction of airway eosinophilia and Th2 cytokines and concomitant increase of T regulatory cells and IL-10 in the lung and Der p 2-specific IgG2a in the serum. Conclusions The addition of VD3 to a conventional AIT protocol would allow the reduction of allergoid dose needed and therefore, the production costs. Moreover, beneficial immunomodulatory effects have been achieved by the oral administration which might favour the management of the therapy by the patients and their adherence, possibly enhancing the efficacy of the treatment.